Aedes caspius caspius Pall. (Culicidae)—новый хозяин Culicimermis schaknovii (Nematoda, Mermithidae) - Исаева, H.M. (Вестник зоологии, 1977)
Aedes caspius P a 11. is mentioned as the seventh host of Culicimermis schakhovii R u b t s o v et, I s a e v a, 1975. The parasitic stage of this helminth is found in the unusial period of time.